The role of Interleukin-6 (IL-6) in pathogensisof COVID -19 - Noorulhuda F. Khalaf; W. Mohammed, Sinai; Ahmed Y. Hanoon (University of Thi-Qar Journal of Science, 2023)
Dissimilar to all other pandemics in the past five decades, the humanity has been ravaged by the coronavirus disease COVID-19. Starting from its outbreak, the disease’s understanding has advanced quickly; multi-organ involvement is the key factor affecting the prognosis of the disease. Mortality and morbidity are closely related to acute respiratory distress syndrome, renal failure, cardiac failure, liver damage, multi-organ failure, and shock. In the initial phases of viral infection, detecting and controlling pro-inflammatory responses are essential. Throughout patient monitoring, it’s crucial to consider the COVID-19 treatment’s unknowable response. It has been discovered that IL-6 is causally linked to greater mortality. It is a reliable indicator regarding the progression of clinical profile as well as the prognosis of the disease. A highly important cytokine, after the activated macrophages, is it. As a result, a measure for COVID-19 could be the control regarding systemic IL-6 levels in the individuals that have been infected by SARS-CoV-2. This study has demonstrated the significance of IL-6 in COVID-19’s immunopathology